2012
DOI: 10.1089/gtmb.2011.0245
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Promoter Region Methylation Patterns of MGMT, CDKN2A, GSTP1, and THBS1 Genes in Intracranial Meningioma Patients

Abstract: Further research on promoter zone methylation will help expose the methylation profile and pathogenesis of meningiomas, which will consequently guide to a deeper understanding of the pathogenesis of the disease, thus ensuring a better understanding of the prognosis and considering novel treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
2
8
1
Order By: Relevance
“…According to the two-hit model of Knudson, DNA methylation can be a second hit inactivating those tumor suppressors, following genetic mutations which are also often present in meningiomas in this locus (Boström et al 2001 ; Knudson 1996 ). Similar findings concerning DNA methylation in meningiomas were recently published by Aydemir et al ( 2012 ), who found p16INK4A to be methylated in 8.3 % [3/36] of cases and Liu et al ( 2005 ) reporting methylation of this gene in 10 % of samples. Amatya et al ( 2004 ) found methylation of p14ARF gene in 5 of 58 cases of benign meningiomas (8.6 %), 2 of 10 cases of atypical meningiomas (20 %), and 2 of 4 cases of anaplastic meningiomas (50 %).…”
Section: Discussionsupporting
confidence: 86%
“…According to the two-hit model of Knudson, DNA methylation can be a second hit inactivating those tumor suppressors, following genetic mutations which are also often present in meningiomas in this locus (Boström et al 2001 ; Knudson 1996 ). Similar findings concerning DNA methylation in meningiomas were recently published by Aydemir et al ( 2012 ), who found p16INK4A to be methylated in 8.3 % [3/36] of cases and Liu et al ( 2005 ) reporting methylation of this gene in 10 % of samples. Amatya et al ( 2004 ) found methylation of p14ARF gene in 5 of 58 cases of benign meningiomas (8.6 %), 2 of 10 cases of atypical meningiomas (20 %), and 2 of 4 cases of anaplastic meningiomas (50 %).…”
Section: Discussionsupporting
confidence: 86%
“…In the past, several studies focused on investigating promoter methylation mainly using a targeted approach for a limited number of genes [4,68,11,30,14,15,34,38,47]. With time, molecular advances allowed interrogation at a larger number of CpG loci [35] culminating with the methylation assays from Illumina (27k and 450k) interrogating approximately 27.000 and 450.000 CpG loci [74,21].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar way, Goutagny et al [ 34 ] have recently shown by SNP-arrays that the most frequent genomic alteration of meningiomas upon progression to grade III was loss of CDKN2A / CDKN2B . Additionally, inactivation through hypermethylation of CpG islands has also been reported in a smaller proportion of meningiomas, including hypermethylation of CDKN2A/p16 INKa in 8-17% of cases, CDKN2A/p14 ARF in 4-13%, and CDKN2B/p15 ARF in 4% of these tumors [ 17 , 35 ]. All such correlations also appear to have a prognostic impact since meningiomas with 9p21 losses have a significantly shorter survival and a worse clinical outcome than cases showing no alterations of chromosome 9p21 [ 36 ].…”
Section: Introductionmentioning
confidence: 99%